Employees’ careerist orientation: Who is more careerist in the Nepalese context? - Bhattarai, Ganesh; Shah, Kapil (NCC Journal, 2022)
This article measured the status of employees' careerist orientation, which is characterized as a preference for seeking job progression via methods that are not performance-based. Significantly, this study was carried out to measure those who are more careerist oriented according to their demographic groups. Perception-based primary data were collected from the employees working in the Nepalese Banking Industry. Five hundred and forty-six respondents were surveyed and analyzed quantitatively with the help of SPSS. Data analysis revealed that employees working in the banking industry believe that career advancement is not possible through performance alone. Moreover, this study exposed several findings (a) employees with a bachelor's degree or below were more career-minded than those with a master's degree or above, (b) female employees were more careerist oriented than their male counterparts, and (c) permanent employees' careerist orientation was greater than temporary employees. Based on the results of this study, numbers the implications and directions for further research were highlighted.